Missed diagnosis of anterior urethral valve complicated with a foreign body: A cause for concern - Nayyar Rishi; Chavda Sundeep; Singh Prabhjot; Gupta Narmada (African Journal of Paediatric Surgery, 2011)
Anterior urethral valve (AUV) is a long known but rare anomaly, which is occasionally encountered in boys with obstructive uropathy. We present a case of AUV with a diverticulum which was misdiagnosed at other center as neurogenic bladder resulting in chronic renal failure. The case was further complicated by breakage of tip of the catheter used for clean intermittent catheterization (CIC) in the diverticulum presenting as a foreign body in the urethra. This article highlights the frequently missed diagnosis of AUV by most practitioners wrongly labeling it as neurogenic bladder, leading to improper management and renal failure in young boys.